ChemInform Abstract: Direct One‐Pot Synthesis of Nucleosides from Unprotected or 5‐O‐Monoprotected D‐Ribose. Issue 6 (21st January 2016) - Downey, A. Michael; Richter, Celin; Pohl, Radek; Mahrwald, Rainer; Hocek, Michal
Abstract: The unprotected D‐ribose (I) reacts with nucleobases [e.g. (II)] to give β‐pyranosyl nucleosides [e.g. (III)] as the major products and β‐furanosides [e.g. (IV)] as the minor products.